Impact of qualitative and quantitative variations in nitrogen supply on catch-up growth in food-deprived-refed young rats. Issue 3 (June 2016) - Bortolotti, Murielle; Ventura, Gabrielle; Jegatheesan, Prasanthi; Choisy, Caroline; Cynober, Luc; De Bandt, Jean-Pascal
Summary: Background: Optimization of the refeeding strategy for the management of malnutrition in early life may enable to improve the quality of catch-up growth. While some data suggest better assimilation of peptides rather than whole proteins the evidence are scarce. Objective: To compare the nutritional properties of peptides, partially hydrolyzed proteins or whole proteins in food-deprived/refed young rats. Methods: Male SD rats (n = 109, 60–70 g) were food-deprived for 48 h and refed for 2–13 days. According to the set of experiments, refeeding was performed at 90% or 100% basal spontaneous intake or ad libitum with either peptide-, partially hydrolyzed protein- or whole protein-containing pediatric enteral nutrition formulas. Body weight, caloric intake and nitrogen balance were measured daily, intestinal trophicity was measured after two-day refeeding, and body composition was determined at the end of the refeeding period. Results: A 2-day food deprivation in young rats led to significant body and organ weight losses, alterations of gut morphology, and decreased plasma citrulline, a marker of gut function. A cautious 2-day renutrition at 90% pre-deprivation level did not restore nutritional status whatever the form of nitrogen supply. A d libitum feeding was shown to be feasible with improved nitrogen efficiency. After 13 days, compared to chow diet, body weight gain was the lowest with peptide- and whole protein-containing diets, and significantly improved with partially hydrolyzed proteins with limited improvement in body lean mass (+8%, NS). Additional experiments indicated that in this model it will be necessary to significantly increase nitrogen supply in order to restore initial body weight and lean body mass. Conclusions: Our results show benefits of ad libitum refeeding on catch-up growth. Our data suggest that partially hydrolyzed proteins may be beneficial in terms of body weight gain but that probably their effectiveness may be improved with higher nitrogen supply.